2022
DOI: 10.3390/ma15217497
|View full text |Cite
|
Sign up to set email alerts
|

Study of the Phase-Change Thermal-Storage Characteristics of a Solar Collector

Abstract: A combined solar phase-change thermal-storage heating system is proposed, wherein erythritol is used as the phase-change material (PCM) used to fill the thermal-storage device, and the storage cavity is heated and stored with a disc concentrator. The Solidification/Melting, Volume-of-Fluid (VOF) model of ANSYS Fluent software was used to simulate the phase-change process of erythritol inside the thermal-storage device. The thermal-storage device was designed based on our numerical calculations, and its perform… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 31 publications
0
3
0
Order By: Relevance
“…Within this chamber, a blend of PCM and air was introduced. Our previous research indicated that an 80% PCM concentration resulted in optimal energy storage efficiency ( Deng et al, 2022 ). The system efficiently captures solar energy, directing it towards the bottom and central conduit, which consequently facilitates the PCM transition from solid to liquid, enhancing solar energy storage.…”
Section: Methodsmentioning
confidence: 99%
“…Within this chamber, a blend of PCM and air was introduced. Our previous research indicated that an 80% PCM concentration resulted in optimal energy storage efficiency ( Deng et al, 2022 ). The system efficiently captures solar energy, directing it towards the bottom and central conduit, which consequently facilitates the PCM transition from solid to liquid, enhancing solar energy storage.…”
Section: Methodsmentioning
confidence: 99%
“…The potential for obtaining eutectic mixtures is vast, as each addition expands the temperature range of the phase change compounds (PCM). Table 8 provides an overview of the most-used eutectic types along with their corresponding eutectic points [49][50][51][52][53]. the phase change compounds (PCM).…”
Section: Eutectic Typementioning
confidence: 99%
“…the phase change compounds (PCM). Table 8 provides an overview of the most-used eutectic types along with their corresponding eutectic points [49][50][51][52][53]. The most promising method that has been considered for latent heat storage is the utilization of molten salt mixtures as phase-change materials [54]: the study focused on the binary salt mixture of lithium chloride-lithium hydroxide (LiCl-LiOH) as a potential phase-change material for thermal energy storage.…”
Section: Eutectic Typementioning
confidence: 99%
“…Different studies have been performed to observe the impact of container tilt angle on the performance of PCM-based TESU [ 23 , 24 , 25 , 26 ]. Babak Kamkari et al [ 23 ] investigated the impact of different inclination angles of the PCM container on the melting behavior of the PCM.…”
Section: Introductionmentioning
confidence: 99%
“…The maximum melting rate was observed for inclination angle of 45°. Yuxuan Deng et al [ 26 ] studied the thermal performance of erythritol-based LHTES utilizing solar heat.…”
Section: Introductionmentioning
confidence: 99%